Prenatal stress induces a depressive-like phenotype in adolescent rats: The key role of TGF-β1 pathway - Fidilio, Annamaria; Grasso, Margherita; Caruso, Giuseppe; Musso, Nicolò; Begni, Veronica; Privitera, Anna; Torrisi, Sebastiano Alfio; Campolongo, Patrizia; Schiavone, Stefania; Tascedda, Fabio; Leggio, Gian Marco; Drago, Filippo; et al. (Frontiers in Pharmacology, 2022)
Stressful experiences early in life, especially in the prenatal period, can increase the risk to develop depression during adolescence. However, there may be important qualitative and quantitative differences in outcome of prenatal stress (PNS), where some individuals exposed to PNS are vulnerable and develop a depressive-like phenotype, while others appear to be resilient. PNS exposure, a well-established rat model of early life stress, is known to increase vulnerability to depression and a recent study demonstrated a strong interaction between transforming growth factor-β1 (TGF-β1) gene and PNS in the pathogenesis of depression. Moreover, it is well-known that the exposure to early life stress experiences induces brain oxidative damage by increasing nitric oxide levels and decreasing antioxidant factors. In the present work, we examined the role of TGF-β1 pathway in an animal model of adolescent depression induced by PNS obtained by exposing pregnant females to a stressful condition during the last week of gestation. We performed behavioral tests to identify vulnerable or resilient subjects in the obtained litters (postnatal day, PND>35) and we carried out molecular analyses on hippocampus, a brain area with a key role in the pathogenesis of depression. We found that female, but not male, PNS adolescent rats exhibited a depressive-like behavior in forced swimming test (FST), whereas both male and female PNS rats showed a deficit of recognition memory as assessed by novel object recognition test (NOR). Interestingly, we found an increased expression of TGFβ-R2 receptor in the hippocampus of both male and female resilient PNS rats, with higher plasma TGF-β1 levels in male, but not in female, PNS rats. Furthermore, PNS induced the activation of oxidative stress pathways by increasing inducible nitric oxide synthase (iNOS), NADPH oxidase 1 (NOX1) and NOX2 levels in the hippocampus of both male and female PNS adolescent rats. Our data suggest that high levels of TGF-β1 and its receptor TGFβ-R2 can significantly increase the resiliency of adolescent rats to PNS, suggesting that TGF-β1 pathway might represent a novel pharmacological target to prevent adolescent depression in rats.